ANALISIS PENDAPATAN BUMDes RAMBAH MUDA JAYA DESA RAMBAH MUDA ROKAN HULU - Irwansyah, Reno (Jurnal Mahasiswa Prodi Manajemen Fakultas Ekonomi, 2013)
Income represent something that of necessary for company. Because of important income require to be done bookkeeping to know how far income which have been obtained from one period to next periodthis research is done by BUMDes that address in Rambah Muda village, District Of Rambah Hilir, Sub-Province of Rokan Hulu is called by BUMDes Rambah Muda Jaya. The Document is used is formal document by BUMDes Rambah such as Financial Statement and Household Budget of BUMDes.